PENGARUH DIMENSI KUALITAS PELAYANAN TERHADAP KEPUASAN MASYARAKAT DI POSYANDU BALITA SAMBILOTO A MANTRIJERON YOGYAKARTA - Susyana Candra Santi Dewi (VISIKES: Jurnal Kesehatan Masyarakat, 2020)
Posyandu is a basic activity of, by and for the community assisted by health workers and cadres. In this era of service quality is seen as one of the tools to achieve competitive advantage, because service quality is one of the factors that determine community satisfaction. Quality of service is a level of excellence that is expected to meet the wishes of the community.Research Objectives: To determine the effect of the dimensions of service quality on community satisfaction in toddlers' posyandu at the Sambiloto A Posyandu in the village of Minggiran Suryodiningratan Mantrijeron Yogyakarta.This type of research with quantitative methods that use a specific population and sample, this research was carried out in the Posyandu Sambiloto A village in the village there were 8 active cadres. sampling technique using simple random sampling and a total population of 19 people consisting of 18 women (mothers) and 1 man (father), correlation analysis used independent variables and dependent variables.The results of the analysis of the T test, the reliability variable t value of 3.092 and significant 0.09 can be interpreted that the significant value of 0.009 is smaller than 0.05 and the value of t is 3.092 greater than t (table) 2.145.Conclusion: That there is an influence between the reliability dimension with community satisfactionKeywords: Competitive, Quantitative, Correlated